(untitled) (Journal of Preventive and Social Medicine, 2021)
Background: Electronic devices are the latest exquisite invention of our modern life and it makes our life so easy and comfortable. Electronic gadgets are now used by the primary school children in a wider scale during the COVlD-19 pandemic. It is imperative to explore its effect of daily life and health of the school children. The objective of the study was to determine the technological interaction of the children and how it is affecting their daily routine, grades and physical health. Methods: This is a cross-sectional study among the students of grade four. A total 340 students were selected by random sampling method from four schools. Data were collected by face to face interview with a structured pretested questionnaire. The study was conducted at Dhanmondi Govt. Boys’ High School, Kamrunnessa Govt. Girls School, Dhanmondi, Bangladesh International School and College (BISC), Mohakhali and SOS Hermann Gmeiner College, Mirpur, Dhaka, Bangladesh. Data were collected from May to October, 2019. Data analysis, findings and results were prepared in November and December, 2019. Results: Among 340 respondents of this study, maximum (78.2%) students watch TV daily, 55.9% of them play with the mobile every day and half (50%) of the students use the tablet daily. Majority (79.7%) respondents have internet at their home and 36.5% of them use the net alone. The causes of usage are- 37.9% students use for entertainment purpose, 26.5% use for education purpose and 34.4% use for both entertainment and education purpose. Conclusion: Children are the future generation of our country. So, it is a prime need to look into this problem and protect our children from the threat of electronic gadget use. JOPSOM 2020; 39(1): 78-87